(untitled) (International Journal of Studies in Nursing, 2016)
Purpose: This pilot study aims to identify factors associated to roofless own health self-perception. Design: Cross-sectional study with a sample of homeless people (n=68) who come for help to one of the homeless service centers founded by a non-profit organization. Socio-demographic characteristics, years living on streets, unhealthy habits, chronic morbidity, basic needs and self-reported physical and mental health were described. To identify factors related to mental and physical health from roofless own perspective, a binary logistic analysis was held. Findings: The majority of participants were under 40 years, male and Spanish, alcohol or drug consumers, 80% have lived in the street for one to five years with high levels of pain and poor mental health conditions. Living on the street over a year, exposure to violence, lack of hygiene and female gender, affect negatively the own perception of physical and mental health conditions. Conclusions: Our results show the different and complex homeless health needs. Given the duration of homelessness affected their health condition, recent roofless homeless should be identified as soon as possible. Clinical relevance and further research: Those providing care for homeless people must promote a more coordinated care, maximizing flexibility and fostering relationships to better response to the multiple and different needs of this one vulnerable population. Further study is needed to allow identify the different experiences of homeless women and men.